Assessment the Wound Healing Efficiency of the Microbial Produced Alginate and the Extract of Persian Mannaplant in the Rat Wounds: the Complex of the Modern and Traditional Dressings - Parastoo Pourali; Leila Khojasteh; Bijan Fahimi; Fatemeh Moghimian; Behrooz Yahyaei (Institue of Medicinal Plants, ACECR, 2019)
Background: Achievement the new biocompatible wound dressing is one of the attractive areas of research. Objective: The present study attempts to examine the healing effects of the alginate - Persian mannaplant extract in the induced rat wounds. Methods: After culturing and detecting of the Pseudomonas aeroginosa strains by phenotyping and genotyping methods, the produced alginate was extracted and used for cell cytotoxicity assessment by MTT assay. 1.5×1.5 cm wounds were made on the tested rat skins. The animals were divided in 4 groups (n= 8). Three groups were equally treated for 21 days with nontoxic doses of alginate hydrogel, herb extract, and alginate hydrogel- herb extract, respectively. The forth group remained as the negative control. In different days after treatments 2 rats from each group were selected and the wound areas and the effects of each material were analyzed. Results: Alginate was extracted from P. aeruginosa strain K1. Results from the macroscopic examination showed that the wound contraction percentage in alginate hydrogel and alginate hydrogel- Persian mannaplant groups had significance difference with the rest other groups (P value < 0.05). Microscopic examination showed that the best group was the one which was treated by alginate hydrogel- Persian mannaplant complex. Conclusion: Although both materials had a good ability to heal the wounds but microscopic examinations showed that the alginate hydrogel- Persian mannaplant complex had better activity in the wound site.